Effect of Feeding Panicum (Mombasa) on Flora Microorganisms in Rumen Sheep - Jameel, Zahraa Mousa; Al-Bayati, Majid H. R. (Journal of agricultural, environmental and veterinary sciences, 2020)
This experiment was conducted on the farm of animal Production Department / College of Agriculture / University of Diyala. the period from 7/5/2019 to 28/5/2019 for a period of 21 days، and the experiment aimed to study the effect of plant nutrition Panicum on the total number of microorganisms in the sheep and the extent of their impact With the quality of feed intake. Nine ewes (non-pregnant) with an average weight of (25.00 ± 0.527) kg were processed from the field of livestock department of the College of Agriculture، University of Diyala، ranging in age from one to two years، animals were randomly divided into three groups and by three Animals for each group، in this experiment followed the individual feeding system، where ewes were placed in cages each area of 1 × 1.5 meters and provided each cage with a feed and a metal manhole and gave her water and cubes of mineral salts free and divided the transactions as follows: First treatment (control): - Feed Concentrated by 3% of animal weight+ hay to the extent of saturation Intent: - feed center by 3% of the weight of the animal+ Drees Panicum limit satiated. The third treatment: - Concentrated feed by 3% of the weight of the animal+ Green panicum to the extent of saturation. The rumen fluid was withdrawn from the experimental animals two weeks after the start of the experiment، at the beginning of the week، the middle of the week and the weekend at times 0، 3 and 6 hours after morning feeding. Immediately after the rumen liquid is withdrawn the pH is measured by the PHep Tester، counting bacterial colonies in the plate count to identify the number of colonies growing in the culture medium.The results of the study were as follows: The presence of significant differences in the pH level of the level of significance p< 0.01 and the superiority of treatment hay Alpanicum and green Alpanicum.the presence of significant differences in the total number of bacteria with a significant level of p
Keywords: Panicaum; Total number of bacteria pH